Aqueous upgrading of ethanol to higher alcohol diesel blending and jet fuel precursors over Na-doped porous Ni@C nanocomposite. (15th September 2022) - Zhong, Quanwang; Liao, Junwei; Zhang, Qian; Qiu, Songbai; Meng, Qingwei; Wu, Xiaoping; Wang, Tiejun
Graphical abstract: Highlights: Na-doped porous Ni@C nanocomposite with excellent water-tolerance was developed. The phase-transfer and alkalinity of catalyst promoted the secondary upgrading. Higher alcohol with C8 + selectivity of 33.8% was achieved as jet fuel precursors. Abstract: Developing biomass-derived fuels is a highly competent approach towards the current serious carbon emission issue caused by fossil fuel. The direct upgrading of the aqueous bio-ethanol to higher alcohols as diesel blending and bio-jet fuel precursors showed great potential in techno-economic. In this work, a water-tolerant Na-doped porous carbon encapsulated Ni nanocomposite was fabricated by direct pyrolyzing of Na-containing organic precursors for direct upgrading of aqueous ethanol. The higher alcohols yield of 35.0 C-mol% with C4-C7 selectivity of 51.9% and C8-C16 selectivity of 33.8% were achieved. The C4-C7 alcohols showed the excellent inter-miscibility with diesel at the 0–90% blending proportion. The C8-C16 higher alcohols with iso/n-OH (isomerized/normal alcohol) ratio of 1.86 can be directly used to produce desired jet fuel by hydrodeoxygenation treatment. Experiment and characterization results indicated that the Ni@C catalyst could spontaneously transfer from aqueous phase to the produced oil (higher alcohols) phase. The coupling of phase-transfer and basic sites of Ni@C-NaGlu effectively promoted the secondary CC coupling of higher alcohols to form C8-C16 alcohols. In general, this work provides a novel feasible approach to produce higher alcohol diesel blending and bio-jet fuel precursors from widely available bio-ethanol.